Effects of rotigotine on daytime symptoms in patients with primary restless legs syndrome: a randomized, placebo-controlled study. (2nd January 2016) - Garcia-Borreguero, Diego; Allen, Richard; Hudson, John; Dohin, Elisabeth; Grieger, Frank; Moran, Kimberly; Schollmayer, Erwin; Smit, René; Winkelman, John
Abstract: Objective: This 12 week double-blind, placebo-controlled study (ClinicalTrials.gov: NCT01569464) was conducted to evaluate the effects of rotigotine transdermal patch on daytime symptoms in patients with idiopathic restless legs syndrome (RLS). Methods: Adult patients with moderate-to-severe RLS were randomized to rotigotine (optimal dose: 1–3 mg/24 h) or placebo. A modified four-assessment version (4:00 pm, 6:00 pm, 8:00 pm, and 10:00 pm) of the Multiple Suggested Immobilization Test (m-SIT) was performed at baseline and end of 4 week maintenance (EoM). Primary study outcomes were change from baseline to EoM in International Restless Legs Syndrome Rating Scale (IRLS) and in average of means for the m-SIT Discomfort Scale (m-SIT-DS) (combined average of mean values from each of the individual assessments). Secondary outcomes included average of means of Periodic Limb Movement during Wakefulness Index (PLMWI; PLM/hour) for the combination of m-SIT. Results: A total of 150 patients were randomized and 137 (rotigotine: 92/101 [91.1%]; placebo: 45/49 [91.8%]) completed maintenance. All 150 randomized patients were assessed for efficacy. At EoM, mean change in IRLS was −14.9 ± 9.3 with rotigotine vs. −12.7 ± 7.6 with placebo (ANCOVA, LS mean treatment difference [95% CI]: −0.27 [−2.96, 2.42]; p = 0.8451). Changes in average of means of m-SIT-DS values of each individual SIT were comparable with rotigotine (−2.68 ± 2.31) vs. placebo (−2.62 ± 2.61) (ANCOVA, LS mean treatment difference [95% CI]: 0.07 [−0.61, 0.75]; p = 0.8336) and comparable reductions in PLMWI were observed in both treatment groups (8.34 [−8.50, 25.17]; p = 0.3290). Rotigotine was generally well tolerated. Application site reactions (rotigotine: 20 patients [19.8%]; placebo: 4 [8.2%]) and nausea (16 [15.8%]; 3 [6.1%]) were the most common AEs. Conclusions: Rotigotine was beneficial in improving overall RLS symptom severity (assessed by IRLS) and RLS symptom severity at various times of the day (m-SIT-DS); however, superiority to placebo was not established.